A critical analysis of organizational transformation – PSR. Issue 2 (13th May 2020) - Naslund, Dag; Wlliamson, Steven
Abstract : Purpose: Hunter Harrison, CEO of the railroad company CSX, died on December 16, 2017. Harrison, known as the railroad transformation guru, was a controversial person. While his transformations were applauded by investors, they were also subject to significant criticism. The author changes triggered service disruptions, customer complaints and federal scrutiny. The purpose of this paper is to conduct an in-depth analysis of the transformation at CSX and to develop a framework for the analysis of organizational transformation projects. Design/methodology/approach: The authors critically analyze the transformation at CSX – known as precision scheduled railroading (PSR). The authors base the initial analysis on the Lean approach to organizational change the authors compare and contrast the two approaches and the authors highlight both positive and negative aspects. The empirical data was collected via two rounds of interviews with employees at CSX – the first informal, the second structured. The lack of academic articles dealing with PSR, the authors focused on the review on trade and newspaper articles. Findings: First, while many transformations are conducted under the assumption that they will improve both effectiveness and efficiency, they are in reality often mainly efficiency improvement programs that can, in fact, hurt both effectiveness and employee morale. Second, the paper presents a framework for the analysis of transformation projects. Research limitations/implications: The authors identify factors for analysis of transformation programs and the authors develop a framework, which structures significant change aspects into three categories, namely, purpose, process and people. Practical implications: Organizations can use the framework to understand the requirements for successful transformation, to analyze if the chosen method matches the organizational strategy and to facilitate successful implementation in the companies. Originality/value: This is the first research paper on PSR and the first paper contrasting PSR with other transformation methods.